Challenging the dogma of colorectal peritoneal metastases as an untreatable condition: Results of a population-based study. (September 2016) - Razenberg, Lieke G.E.M.; Lemmens, Valery E.P.P.; Verwaal, Victor J.; Punt, Cornelis J.A.; Tanis, Pieter J.; Creemers, Geert-Jan; de Hingh, Ignace H.J.T.
Abstract: Purpose: To determine the impact of the implementation of novel systemic regimens and locoregional treatment modalities on survival at population level in colorectal cancer (CRC) patients presenting with peritoneal metastases (PMs). Methods: All consecutive CRC patients with synchronous PM (<3 months) between 1995 and 2014 were extracted from the Eindhoven area of the Netherlands Cancer Registry. Trends in treatment and overall survival were assessed in four time periods. Multivariable regression analysis was used to analyse the impact of systemic and locoregional treatment modalities on survival. Results: A total of 37, 036 patients were diagnosed with primary CRC between 1995 and 2014. Synchronous PM was diagnosed in 1, 661 patients, of whom 55% had also metastases at other sites (n = 917) and 77% received anticancer therapy (n = 1, 273). Treatment with systemic therapy increased from 23% in 1995–1999 to 56% in 2010–2014 (p < 0.0001). Cytoreductive surgery with hyperthermic intraperitoneal chemotherapy (CRS-HIPEC) was applied since 2005 and increased from 10% in 2005–2009 to 23% in 2010–2014. Surgery for lymphatic or haematogenous metastases increased from 2% to 10% in these periods. Median overall survival of the complete cohort improved from 6.0 months in 1995–2000 to 12.5 months in 2010–2014 (p < 0.0001), with a doubling of survival for both PM alone and PM with other involved sites. The influence of year of diagnosis on survival (hazard ratio, 2010–2014 versus 1995–1999; 0.5, 95% confidence interval: 0.43–0.62; p < 0.0001) disappeared after including systemic therapy and locoregional treatment modalities in subsequent multivariable models. Conclusion: CRC patients presenting with PM are increasingly offered a multidisciplinary treatment approach, resulting in an increased overall survival for the entire cohort. Highlights: A total of 1, 661 patients with synchronous peritoneal metastases (PM) of primary colorectal cancer (CRC) between 1995 and 2014. Intensified use of systemic therapy; 23% in 1995–1999 to 56% in 2010–2014. Increasing use of cytoreductive surgery with hyperthermic intraperitoneal chemotherapy; 10% in 2005–2009 to 23% in 2010–2014. Increased overall survival for the entire cohort of CRC patients with PM. Improved survival rates are associated with the increasing use of a multidisciplinary treatment.